Conversion of Hazardous Motor Vehicle Used Tire and Polystyrene Waste Plastic Mixture into useful Chemical Products - Sarker, Moinuddin; Rashid, Mohammad Mamunor (European Journal of Sustainable Development, 2014)
Motor vehicle used tire and polystyrene waste plastic mixture into fuel recovery using thermal degradation process in laboratory batch process. Motor vehicle used tire and polystyrene waste plastic was use 75 gm by weight. Motor vehicle tire was 25 gm and polystyrene waste plastic was 50 gm. In presence of oxygen experiment was performed under laboratory fume hood. Thermal degradation temperature range was 100 - 420 oC and experiment run time was 5 hours. Product fuel density is 0.84 gm/ml and liquid fuel conversion rate was 54.93 %. Fuel was analysis by GC/MS and compounds are present aliphatic group, aromatic group, alcoholic group, oxygen content and nitrogen content. Fuel can use refinery process as a refinery feed. Keywords: Tire, polystyrene, conversion, chemical product, vehicle, hydrocarbon